Hubungan Matan dan Syarah Ta’līm Al-Muta’allim Ṭarīq Al-Ta’allum dengan Daulah ‘Aliyyah Utsmaniyyah serta Implikasinya dalam Pendidikan Islam di Nusantara - Tatang Hidayat; Syahidin Syahidin; Arif Noor Dhaiman (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2020)
The purpose of this study was to analyze the relationship of matan and syarah Ta'līm al-Muta'allim Ṭarīq al-Ta'allum with Daulah 'Aliyyah Uthmaniyyah and its implications in Islamic education in the Archipelago. Islamic education is fixed in terms of teaching materials and learning methods, because it is part of sharia law that relies on evidence, while uslub (technique) and its facilities are constantly evolving. From this point of view, the analysis of the Book of Ta'līm al-Muta'allim Tarīq al-Ta'allum and its implications in Islamic education in the Archipelago can be reviewed. This research uses qualitative approaches and descriptive methods. Based on the results of the research, the book ta'lîm al-Muta'allim Tarīq al-Ta'allum and its syarah reached the Archipelago through the relationship of Mecca as part of the Territory (governorate level/ Province) of Daulah 'Aliyyah Ottoman who was the Caliphate of the Muslims at that time with the Jawi Scholars who studied there. The Book of Ta'lîm al-Muta'allim Ṭarīq al-Ta'allum and its syarah are clearly seen in the Salafiyyah (Traditional) Pesantren Curriculum especially in Java Island. It can be determined that the